Tobacco Use: Quitting Plan, Attempts and Obstacles for Cessation- A Cross-Sectional Study from A Sub-Urban Neighbourhood of Chennai-Tamil Nadu - TP Jayanthi; V Subhashini; Anantha Eshwar VM (Medsci Publications, 2023)
Introduction: Tobacco consumption is a preventable public health problem. GATS -2 survey in Tamil Nadu shows that 20% of adults use tobacco, 40% had plans to quit and 48% had made quit attempts. The purpose of the study was to assess factors associated with tobacco use; quitting plan, attempts and identify obstacles for to-bacco cessation. Methods: A Cross-sectional study was done among 300 tobacco users in a suburban neighbourhood of Chennai and data was analysed using SPSS software. Results: Ninety five percent were smokers and 86% smoked cigarettes. 70% knew that it causes cancer and res-piratory diseases. 60% planned to quit, 69% made quit attempts. Those with quit plans and health problems had an increased odds (AOR of 1.02 and 1.004 respectively) of making quit attempts. Advice from health profession-als (48%) and family (52%) triggered quit attempts. Stress and work pressure were obstacles for quitting (70%). Availability of therapy and professional help for tobacco cessation was known only to 49% and 14.7% respec-tively and none availed it. Conclusion: Awareness of health hazards of tobacco use was high. Quit attempts have increased but with high failure rates due to lack of information and access to tobacco cessation services. Provision of community and fa-cility-based tobacco cessation services and integration with existing health programmes is the present need.